Proteome-Wide Analysis of Lysine 2-Hydroxyisobutyrylation in Candida albicans - Hailin Zheng (American Society for Microbiology, 2021)
ABSTRACT Candida albicans is the most common human fungal pathogen, causing diseases ranging from mucosal to systemic infections for both immunocompetent and immunocompromised individuals. Lysine 2-hydroxyisobutyrylation is a highly conserved posttranslational modification found in a wide variety of organisms. In this study, we surveyed the biological impact of 2-hydroxyisobutyrylation on lysine residuals (Khib) in C. albicans. Using an antibody enrichment approach along with the traditional liquid chromatography-tandem mass spectrometry (LC-MS/MS) method, we analyzed the pattern of Khib-modified proteins and sites in one wild-type strain of C. albicans. We identified 1,438 Khib-modified proteins with 6,659 modified sites in this strain, and a more detailed bioinformatics analysis indicated that the Khib-modified proteins are involved in a wide range of cellular functions with diverse subcellular locations. Functional enrichment analysis featured several prominent functional pathways, including ribosome, biosynthesis of antibiotics, biosynthesis of secondary metabolites, biosynthesis of amino acids and carbon metabolism, of which the ribosome pathway is the most affected pathway. Even compared with the reported numbers of lysine acetylation (Kac) and succinylation (Ksuc) sites, the numbers of Khib-modified sites on ribosomal proteins remained the highest for C. albicans. These bioinformatic results suggest that 2-hydroxyisobutyrylation may play an indispensable role in the regulation of the ribosomal biogenesis and protein translation. Findings in this study may provide new insights for studying posttranslational modification (PTM)-associated mechanisms in fungal development and pathogenicity. IMPORTANCE C. albicans is one of the most commonly reported fungal pathogens in mucosal and systemic infections. A better understanding of its growth habits and metabolic processes in the host should help improve defense strategies. The newly discovered protein posttranslational modification (PTM) on histones is one epigenetic mechanism which has been linked to many pathogenic events, including cancers. The types of PTM and their pathogenic roles in C. albicans are still somewhat poorly understood, even though studies of C. albicans based on acetylation inhibitors have shed some light on their function, and it seems that PTMs regulate pathogenic adhesion factors. Here, we quantified and analyzed the occurrence of lysine 2-hydroxyisobutyrylation (Khib) in C. albicans. The Khib-modified proteins are enriched with respect to carbon metabolism, ribosomal biogenesis, and protein translation in C. albicans.